ESG performance, investor attention, and company reputation: threshold model analysis based on panel data from listed companies in China - Meng, Tiantian; Dato Haji Yahya, Mohamed Hisham; Mohd Ashhari, Zariyawati; Yu, Danni (Elsevier, 2023)
Amid heightened inter-company competition and the global drive towards ESG reforms, this study investigates whether enhancing the ESG performance of listed companies in China assists in elevating their reputation. It also examines the mediating role of investor attention in the relationship between ESG performance and company reputation, and further delves into whether theres a threshold effect of investor attention on the ESG-performance relationship. Utilizing sample data from Chinese listed companies spanning 2011 to 2021, and employing methods such as the panel two-way fixed-effects regression model, mediation effect testing, and threshold effect models, the study reveals that there is a significant positive relationship between ESG performance and the reputation of these companies. Moreover, a unique threshold effect is observed in the relationship between ESG performance and reputation. Innovatively, our research confirms the mediating role of investor attention in the relationship between ESG performance and company reputation, noting a more pronounced mediation effect in non-state-owned companies as opposed to state-owned ones. This study builds upon the existing literature on the relationship between CSR and company reputation, as well as between investor attention and reputation. By elucidating the mediating role of investor attention and its dual threshold effect, we provide a nuanced perspective on how ESG performance influences company reputation. Practically speaking, this research offers strategic recommendations for companies, investors, and regulators in the Chinese market on reputation management aligned with ESG principles. For instance, companies should prioritize their ESG performance, striving to maintain it above the market average, thus optimizing its effect on their reputation. Furthermore, companies should nurture their relationships with investors, aiming to elevate investor attention above the market mean. Policymakers should encourage companies to bolster their ESG performance, even contemplating more rewards and incentives for those with notable ESG achievements. Lastly, auditors should intensify their focus on non-financial information during audits, especially ensuring the accuracy and completeness of a companys ESG reports.